DETERMINAN BESARAN BEDA TEMPORER BEBAN PAJAK TERHADAP PRAKTEK INCOME SMOOTHING - Diyah Probowulan (Jurnal Ilmiah Akuntansi Indonesia, 2019)
The differences between the accounting principles of taxation rules require managers to make two types of income statement. Commercial income statement prepared on Financial Accounting Standards, while fiscal income statement is based on the tax regulations. The difference between profit before tax and taxable income caused by the differences between the concepts of tax accounting in the recognition of income and expenses. In the context of income tax accounting, these differences result in two different types (temporary / timing differences) and difference remain (permanent differences). Statement of Financial Accounting Standards (SFAS) No. 46, Accounting for Income Taxes. Several studies have described that the amount of temporary differences in the tax burden of the deferred tax assets can be an instrument of earnings management (Miller amp; Skinner, 1998; Chao, et al., 2004; Frank amp; Rego, 2006; and Schrand amp; Wong, 2003). The amount of the tax burden in the deferred tax asset can affect operating profits run; and in SFAS No. 109 are described on the company, earnings in future periods as a whole, which it includes subjectivity is considered. The result, in the research: non-deductible expense does not affect the practice of high and low income smothing and deductible expense does not result in a change in company practices income smothing.